Glenn close 101 dalmations - Hughes, John; Herek, Stephen (USA : Walt Disney Pictures [production company] ; Kuala Lumpur : Berjaya HVN Sdn. Bhd. [distributor])
101 adorable puppies, one howling good time
Executive producer, Edward S. Feldman ; screenplay, John Hughes, editor, Trudy Ship
Jeff Daniels, Joely Richardson, Joan Plowright
Keywords: Animal in motion pictures; Dogs in motion pictures